Influence of age on the spermiogramic parameters of native sheep (Journal of the Bangladesh Agricultural University, 2010)
The study was conducted to evaluate the qualities of ram semen in different age groups (one to four years) were evaluated. The parameters included testes length (cm), testes breadth (cm), scrotal circumference (cm), live weight (kg), semen volume (ml), PH, sperm concentration (x109), motility (%), percentage of live, dead and normal, abnormal spermatozoa of native sheep. The average semen volume (ml) found to be 0.60, 0.91, 0.85 and 0.87; sperm concentration (109/ml) 1.03, 3.27, 4.45 and 4.17 and finally motility (%) were found to be 68.07, 75.03, 75.01 and 76.25 respectively for the 1st, 2nd, 3rd and 4th year age of native ram. The effects of age on all parameters (testes length, semen volume, semen pH, sperm concentration, motility, viability, normal spermatozoa) were significant except testes breadth and scrotal circumference. The value of all of these parameters increased linearly up to three years with the increase of age except PH. The result of the present study indicated that scrotal diameter, serving capacity; normal and live spermatozoa were comparatively better during the 3rd year than the 1st and 2nd year of age while the values were almost similar at 3rd and 4th year of age. With the increasing of age, the semen quality improved and stabilized up to at the age of 3 years. Keywords: Native sheep; Spermiogramic parameter; Age DOI: 10.3329/jbau.v7i2.4738 J. Bangladesh Agril. Univ. 7(2): 301-304, 2009